Quantitative Analysis of Aqueous Phase Composition of Model Dentin Adhesives Experiencing Phase Separation - Spencer, Paulette; Park, Jonggu; Misra, Anil S.; Ye, Qiang; Laurence, Jennifer S.; Pamatmat, Francis; Parthasarathy, Ranganathan; Marangos, Orestes (My University, 2012)
There have been reports of the sensitivity of our current dentin adhesives to excess moisture, for example, water-blisters in adhesives placed on over-wet surfaces, and phase separation with concomitant limited infiltration of the critical dimethacrylate component into the demineralized dentin matrix. To determine quantitatively the hydrophobic/hydrophilic components in the aqueous phase when exposed to over-wet environments, model adhesives were mixed with 16, 33, and 50 wt % water to yield well-separated phases. Based upon high-performance liquid chromatography coupled with photodiode array detection, it was found that the amounts of hydrophobic BisGMA and hydrophobic initiators are less than 0.1 wt % in the aqueous phase. The amount of these compounds decreased with an increase in the initial water content. The major components of the aqueous phase were hydroxyethyl methacrylate (HEMA) and water, and the HEMA content ranged from 18.3 to 14.7 wt %. Different BisGMA homologues and the relative content of these homologues in the aqueous phase have been identified; however, the amount of crosslinkable BisGMA was minimal and, thus, could not help in the formation of a crosslinked polymer network in the aqueous phase. Without the protection afforded by a strong crosslinked network, the poorly photoreactive compounds of this aqueous phase could be leached easily. These results suggest that adhesive formulations should be designed to include hydrophilic multimethacrylate monomers and water compatible initiators. © 2012 WILEY PERIODICALS, INC.
Keywords: dentin adhesive; hydrophilic; hydrophobic; phase separation; water